Supply Chain Management for Development of The Agroindustry Cassava In Trenggalek District - Dona Wahyuning Laily; Ida Syamsu Roidah; Dita Atasa (Future Science, 2022)
This study aims to determine: the mechanism of supply chain management; chain management model supply; and performance of the cassava supply chain in Trenggalek Regency. Method research is descriptive. The research location was determined intentionally. The data analysis method is descriptive method with the Food Supply Chain Network framework approach according to Vorst dan Performance measurement is done through the calculation of marketing margin and farmer's share. Research result shows that the target market is domestic while the development target is in the form of technology improvement, increased coordination and collaboration, and procurement of formal contractual agreements. Cooperation is carried out on the basis of an oral contract between members, the transaction system is carried out in cash and there is government support in the form of capital, equipment, and resource development training man. The supply chain management model consists of farmers, collectors, market traders, and agro-industry cassava as a chain actor, each of which performs different activities depending on the the inputs and the resulting outputs. The most efficient channel is Channel 1 (Petani (cassava)? market traders (cassava) ? cassava agroindustry). The channel is considered efficient because it has relatively low marketing margin value, relatively high farmer's share and profit and cost ratio higher than other channels.